Analisis Kata Harpazontes Berdasarkan Yudas 1:23 dan Implementasinya Terhadap Penginjilan - Pattinaja, Aska Aprilano; Kiamani, Andris; Manurung, Well Therfine Renward (JURNAL LUXNOS, 2025)
Outreach is a term that is very often heard in the evangelistic movement. The term is generally translated as trying to win lost souls. Interestingly, Jude 1:23 is often used in the context of soul winning with an emphasis on the word harpazontes. The purpose of this study is to put the right perspective on the word harpazontes and its implications from an evangelistic point of view. By using a qualitative method with a hermeneutic exegesis study to conduct a theological study of the word harpazontes, this article finds three results of the analysis of the word harpazontes, namely: first, the context of this word refers to the act of seizing souls who have repented only to become shaky and go back astray; second, the context of this word is different from the word "reaching" which refers more to new souls who have not heard of salvation; and third, in its implementation, every believer must also be vigilant and careful in service so as not to fall into sin. This research is a reference for information and opens insights into every evangelistic movement to continue to have compassion for souls and dare to snatch them from the fire.